Avoiding hunger or attaining fullness? Implicit goals of satiety guide portion selection and food intake patterns - Cheon, Bobby Kyungbeom (2020)
Although implicit theories have been studied in the context of personal traits, there has been limited investigation of their role in physiological domains such as appetite. Subjective feelings and affective states can function as goals and desired end states that individuals regulate their behaviors to attain. Likewise, different conceptualizations people maintain for the subjective experience of satiety (i.e., terminating hunger or attaining fullness) may also predict individual variations in eating behavior. We examined whether portion selection and food intake were guided by such implicit goals pertaining to the nature of satiety. Across 3 studies, we observed that individuals report distinct subjective requirements (degrees of fullness) to attain different states of satiety (stop hunger, feel comfortably full, feel completely full), suggesting that these states reflect independent goals or outcomes. Importantly, personal requirements to feel completely full (compared to stop hunger or feel comfortably full) were observed to be the strongest predictor of portion sizes selected in Study 1 (B = 1.17, p < .001) and Study 2 (B = 4.26, p = .004), and the quantity of energy consumed from a meal in Study 2 (B = 3.07, p = .01). Yet, experimentally activating a situational goal to stop hunger (vs. feel full) produced the selection of smaller portion sizes, F(1, 41) = 5.64, p = .02, and personal requirements to stop hunger to become the dominant predictor of portion selection patterns in Study 3 (B = 0.43, p = .005). These findings reveal that eating behaviors of modern consumers may be guided by a predominant goal to attain the subjective experience of complete fullness, although this implicit goal may be malleable to situational demands.